Comparing the Efficacy of Intra-Articular Dexmedetomidine in Combination with Fentanyl versus Fentanyl Alone for Post-surgical Analgesia after Knee Arthroscopy - Smith Kadakia; Sahasrabudhe Anupama D; Chavan Rashmee V (Dr. Annil Mahajan, 2022)
Background: Effective management of post-surgical pain in knee arthroscopy is crucial for early rehabilitation of patients. This study is aimed to analyse the potency of fentanyl when administered intraarticularly alone and in combination with dexmedetomidine for postsurgical analgesia after knee arthroscopy. Methods: Prospective double-blinded randomized controlled study included 60 patients of elective knee arthroscopy. The patients were classified in group I (100-mcg fentanyl) and group II (treated with 100-mcg + 50-μg dexmedetomidine). VAS score and time for foremost requirement of analgesia was documented. Results: The difference in the VAS scores across the two groups was statistically significant for initial 6 hours. In groups I, 18 (60%), and II, 4 (13.33%) patients requested analgesia within 6 hours, whereas 12(40%) and 26(86.67%) patients requested analgesia after 6 hours, respectively. For the foremost requirement of analgesia within and after 6 hours, the difference between the number of patients in group I was statistically insignificant (P = 0.1967), whereas that in group II was statistically significant (P <0.001). Conclusion: Dexmedetomidine when administered intra-articularly in amalgamation with fentanyl provides > 6-hour-long analgesia, lowers degree of postsurgical pain, and requirement for postsurgical analgesia. Therefore, mentioned combination is highly effective and better analgesic than fentanyl alone.